2023
DOI: 10.21037/cdt-22-473
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity related hypertension among overweight or obese adults in River Nile State in Northern Sudan: a community based cross-sectional study

Abstract: Background Reducing excess body weight is important for control and management of high blood pressure (BP) in adults. Previous studies showed high prevalence of hypertension in River Nile State—north of Sudan, hence this study to establish whether obesity can be among the main risk factors and to study the prevalence of obesity related hypertension among Sudanese adults in River Nile State. Methods This was a cross sectional community-based study conducted in River Nile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This is similar to the study findings where the prevalence of hypertension was found to be higher amongst men (50.0%) compared to women (38.0%). Also, the findings are higher than the 30.6% reported in Bangladesh (Ali et al, 2022), 10.8% in Korea (Choi et al, 2018), 40.67% in Nepal (Shrestha et al, 2020), 25.5% in Malaysia (Chua et al, 2017) and 73.7% in Sudan (Noor et al, 2023). The differences in the prevalence of hypertension may be due to the differences in the study design and setting given that some of the studies were hospital based and some were carried out both in an urban and rural setting as opposed to this study which was community based and only involving an urban population of adults.…”
Section: Discussioncontrasting
confidence: 58%
“…This is similar to the study findings where the prevalence of hypertension was found to be higher amongst men (50.0%) compared to women (38.0%). Also, the findings are higher than the 30.6% reported in Bangladesh (Ali et al, 2022), 10.8% in Korea (Choi et al, 2018), 40.67% in Nepal (Shrestha et al, 2020), 25.5% in Malaysia (Chua et al, 2017) and 73.7% in Sudan (Noor et al, 2023). The differences in the prevalence of hypertension may be due to the differences in the study design and setting given that some of the studies were hospital based and some were carried out both in an urban and rural setting as opposed to this study which was community based and only involving an urban population of adults.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies suggest that both obesity and BMI are risk factors for hypertension [ 31 ]. Furthermore, a greater BMI percentile is linked to higher blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that both obesity and BMI are risk factors for hypertension [32]. Furthermore, a greater BMI percentile is linked to higher blood pressure.…”
Section: Correlation Of Bmi and Bpmentioning
confidence: 96%